Turkey-MIDDLE EAST RELATIONS AND BAGHDAD PACT - TANSÜ, Yunus Emre; ARSLAN, Gökhan (SSD Journal, 2018)
With the outbreak of the Second World War, the USSR has evolved into a bipolar structure around. Turkey and the Arab threat detection with this process are completely changed. The real threat was the Soviet Union aimed at spreading south by Turkey. Despite sharing the same geography with Turkey Arabian Arabs as threatening its neighbor the Soviet Union without borders. The real threat to Arabs is Israel and the Western states. Turkey, while turning his face every day in the face of the Soviet threat to Western alliance has begun to turn its back on the Arabs. Turkey, which has more than half of the world's oil reserves, is adjacent to the Middle East, Turkey's secular Western Bloc with a structure that is able to have more intimate relationships, Arab countries to manage for many years, began to emerge Turkey to the forefront of Middle East policy of the West Block after having lived intertwined with them and 1950s with because it is the first Muslim country to recognize Israel. Western opposition in this process consisting in Arab countries began to be reflected in contrast with each passing day Turkey. US and UK with the support of NATO's Middle East extension in order to create a political-military alliance will be in 1955 under the leadership of Turkey has attempted to establish the Baghdad Pact.